Relationship between COVID-19 and ABO blood system: clear and sufficient evidence? (Research, Society and Development, 2021)
Introduction: The ABO blood group is an example of evolutionary adaptation where, for thousands of years, microorganisms and humans interact in a symbiotic or pathological way, influencing the genetics of the populations and the evolution of the human genome by the natural selection of specific alleles capable of modifying pathogens. Objective: to analyze or prognostic meaning of two antigens of two blood groups ABO and Rh together with various parameters in patients accompanied as a diagnosis of COVID-19. Methodology: This is a descriptive research of an integrative literature review type, which seeks to analyze or prognostic meaning of two antigens of two blood groups ABO and Rh, together with various parameters in patients accompanied by a diagnosis of COVID-19. A research was carried out through online access to databases National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Biblioteca Virtual em Saúde (BVS) and EBSCO Information Services, no more than July 2021. Results: The most frequently observed blood type was or A + among patients with COVID-19. The Rh + blood group was found in all cases admitted to UTI with a fatal evolution. Or blood group A was associated with an increased risk of infection, or group O was associated with a reduced risk. Conclusion: There is no way to affirm the association of blood group A positive with COVID-19 with scientifically proven results in different populations. However, the association between blood groups and other past infections cannot be ignored.